2017
DOI: 10.4209/aaqr.2016.02.0084
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical Methods for Filling Gaps in Level-3 Monthly-Mean Aerosol Optical Depth Data from Multi-Angle Imaging SpectroRadiometer

Abstract: The Aerosol Optical Depth (AOD) retrieved from satellite remote sensing measurements such as from MISR and MODIS, both onboard the Terra platform, are widely used for studying regional and global patterns of aerosol loading. Aerosol products from these sensors are also used for analyzing feedbacks and relationship between aerosols and climatic variables including clouds, precipitation, and radiation fluxes. Several statistical techniques leading to the understanding of such relationships, including empirical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition, they found that the dicted maps of PM 10 concentration were substantially different between kriging and co-kriging, with the co-kriging map capturing more of the expected special variation of PM 10 in the domain. In addition, Singh, Venkatachalam, and Gautam (2017) used co-kriging to fill in missing MISr AOD data using observations from the MODIS instruments. However, there is no example of co-kriging with satellite-based PM 2.5 products in the literature.…”
Section: Co-krigingmentioning
confidence: 99%
“…In addition, they found that the dicted maps of PM 10 concentration were substantially different between kriging and co-kriging, with the co-kriging map capturing more of the expected special variation of PM 10 in the domain. In addition, Singh, Venkatachalam, and Gautam (2017) used co-kriging to fill in missing MISr AOD data using observations from the MODIS instruments. However, there is no example of co-kriging with satellite-based PM 2.5 products in the literature.…”
Section: Co-krigingmentioning
confidence: 99%
“…To ensure the data integrity and the accuracy of the interpolation results, several methods have been proposed. Combing multisource AOD data can provide additional AOD information and increase the availability of valid data [18,23,27], which can then be used to generate the desired products, even seamless aerosol products through spatial interpolation methods. In one approach, AOD data were recovered by synthetically weighing the AOD similarity, spatial proximity, and NDVI similarity based on the mechanism of satellite AOD retrieval [28].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable related work has concentrated on multisource AOD dataset fusion or AOD gap-filling methods using different models. The initial and most extensively applied method is interpolation, but the AODs obtained in this way show high spatiotemporal variability; thus, this method is not suitable for application to anticipate missing AOD data (Singh et al, 2017). Another widely used method involves merging mul-tiple AOD products; this method can improve the data quality but often fails to completely eliminate missing pixel values, even bringing about offsetting consequences (Bilal et al, 2017;Ali and Assiri, 2019;.…”
Section: Introductionmentioning
confidence: 99%